(untitled) (Journal Of Educational and Psychological Researches, 2016)
To achieve the goals, the researcher followed the design of equal and independent groups of partial control and post-test . The research has chosen the Institute of Fine Arts in the area Almansour area as deliberate sample where three sections of students have been chosen and the number of students is (69) students. The researcher conducted equivalence in the variables (age, and IQ , and the overall rate for grade III). in diagnostic phase, (21) concepts of alternative image out of (46) concepts have been identified in addition to the goals of formulation of acquisition concepts according to the three processes (definition, discrimination and application). Achievement test has been conducted then after, Multiple choice consists of (63) points to make sure of the students to the concepts of alternative image. It was mad sure of the test sincerity, persistence and the coefficient of difficulty and the coefficient of indistinguishable. The test has been applied on Tuesday, 05.06.2014 where Analysis of variance and (Tukey) tests were used as a statistical means for research data treatment . The following results have been obtained: - 1- The superiority of the first experimental group of students who studied according to Driver model over control group of students who studied according to the traditional way in the post-test. 2- The superiority of the second experimental group of students who studied according to Posner model over the control group students who studied according to the traditional way in the post-test. 3- There, is no difference of statistical significance between the experimental group who studied according to Driver model and the student who studied according to Posner model . In light of the research results, the researcher found a set of conclusions and recommendations and proposals.